2019
DOI: 10.1029/2018jb016143
|View full text |Cite
|
Sign up to set email alerts
|

Teleseismic Waveform Complexities Caused by Near Trench Structures and Their Impacts on Earthquake Source Study: Application to the 2015 Illapel Aftershocks (Central Chile)

Abstract: The complex near trench velocity structures, characterized by strongly varying bathymetry along with seawater, can produce substantial waveform complexities for near trench earthquakes, which makes it difficult to study earthquake source parameters through waveform modeling/inversion. Here we explore these wavefield complexities via modeling teleseismic records of a Mw6.6 near coast event and a Mw6.8 near trench event in the 2015 Illapel earthquake sequence. For the near coast event, the waveforms of direct P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Nonetheless, ambiguity exists regarding which source rupture attributes and source region structural features are important for exciting strong P coda amplitudes (Fan & Shearer, ; Ihmlé & Madariaga, ; Ward, ; Wu et al, ; Yue et al, ). Recent three‐dimensional studies by Qian et al () and Wu et al () conclude that the bathymetry and sedimentary layers have strong effects on enhancing P wave coda oscillations in addition to the location of earthquake slip.…”
Section: Pwpmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, ambiguity exists regarding which source rupture attributes and source region structural features are important for exciting strong P coda amplitudes (Fan & Shearer, ; Ihmlé & Madariaga, ; Ward, ; Wu et al, ; Yue et al, ). Recent three‐dimensional studies by Qian et al () and Wu et al () conclude that the bathymetry and sedimentary layers have strong effects on enhancing P wave coda oscillations in addition to the location of earthquake slip.…”
Section: Pwpmentioning
confidence: 99%
“…For example, a proposed second-stage tsunami earthquake at shallow depth during the source rupture process for the 2015 Illapel (M W 8.4) earthquake was inferred based on observation of prolonged teleseismic P wave ground motions (Lee et al, 2016). However, Lay et al (2016), An et al (2017), and Qian et al (2019) demonstrate that the P coda could be explained without any prolonged rupture by improved modeling of the water reverberations generated by shallow slip. Nonetheless, ambiguity exists regarding which source rupture attributes and source region structural features are important for exciting strong P coda amplitudes (Fan & Shearer, 2018;Ihmlé & Madariaga, 1996;Ward, 1979;Wu et al, 2018;Yue et al, 2017).…”
Section: Pwpmentioning
confidence: 99%
See 1 more Smart Citation
“…These include how P waves which are refracted to near-normal angles at the seafloor are converted to horizontally travelling t-waves in the SOFAR channel (de Groot-Hedlin & Orcutt 2001), how primary microseismic noise with a transverse component is generated (Nishida & Takagi 2016), and how best to isolate or account for water column reverberations, especially over areas rough bathymetry (Blackman et al 1995). The latter of these can significantly complicate understanding of earthquake dynamics (Yue et al (2017), Qian et al (2019)), especially of the largest earthquakes which occur at subduction zones with rough bathymetry (Lay & Rhode (2019), Wu et al (2020)).…”
Section: Introductionmentioning
confidence: 99%
“…The model of Heidarzadeh et al (2016) revealed a broadened region of coseismic slip, and this could be caused by their preset of rupture speed, because the rupture distribution expands proportionally to the rupture velocity. However, it is a well-recognized fact that teleseismic data themselves are insufficient to resolve rupture processes in detail (Delouis et al, 2010), and also, the teleseismic waveforms for sea-land subduction earthquake are vulnerable to water reverberation, bathymetry of the seafloor, and 3-D heterogeneity near trench, resulting in unexplainable phenomena if these effects are ignored during the rupture process inversion (Yue, Castellanos, et al, 2017;Qian et al, 2017). Barnhart et al (2016), Grandin et al (2016), and Klein et al (2017) jointly used GPS static displacements and InSAR data to explore the coseismic slip distribution.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%